3,4-Dihydroxyphenylethanol ameliorates lipopolysaccharide-induced septic cardiac injury in a murine model - Zhang Lu; Wen Kun; Zhang Zhiqiang; Ma Chengen; Zheng Ni (Open Life Sciences, 2021)
3,4-Dihydroxyphenylethanol (DOPET) is a polyphenol found in olive oil. The present study evaluated the protective role of DOPET on LPS provoked septic cardiac injury in a murine model. Four groups were used in the study (n = 3): control, LPS, DOPET alone, and DOPET + LPS. LPS (15 mg/kg; i.p.); they were used to induce cardiac sepsis. The cardiac markers like LDH, CK-MB, and troponin-T, as well as inflammatory cytokines like TNF-α and IL-6 were measured in the serum. The antioxidants and oxidative stress parameters were measured in cardiac tissues. RT-PCR and western blot methods were done to evaluate the expression of inflammatory mediators and apoptotic markers. DOPET significantly decreased the cardiac markers (LDH, CK-MB, and troponin-T) and TNF-α and IL-6 level in the serum. DOPET effectively reduced the levels of MDA and NO in LPS intoxicated rats. DOPET also increased the levels of antioxidants like SOD, CAT, GPx, and GSH in LPS intoxicated rats. The mRNA levels of TNF-α, IL-6, and NF-κB were significantly downregulated by DOPET in cardiac tissues of LPS rats. The protein expression of Bcl-2 was upregulated, and Bax and caspase-3 were downregulated by DOPET. DOPET effectively attenuates LPS-induced cardiac dysfunction through its antioxidant, anti-inflammatory, and anti-apoptotic mechanisms.